2021
DOI: 10.2186/jpr.jpor_2019_345
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of oral mucosal regeneration by low intensity pulsed ultrasound: an in vivo study in a porcine model

Abstract: Purpose: Many studies have shown the ability of low intensity pulsed ultrasound (LIPUS) to stimulate the bone, cartilage and tendon regeneration but only a few studied LIPUS interest in the regeneration of the oral mucosa. The purpose of this study is to assess the ability of LIPUS to stimulate the regeneration of the palatal mucosa in a porcine model. Methods: Ten adults mini-pigs were used. Two mucosal wounds were realised on the left and right side of the palate of each pig. The right side was treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Low-intensity pulsed ultrasound (LIPUS), a form of ultrasound delivers at a low intensity and outputs in the mode of pulsed waves, has been demonstrated as adjuvant physical therapy, including promoting the differentiation of stem cells [ 22 , 23 ], inhibiting inflammatory responses [ 24 ], accelerating soft tissue regeneration [ 25 , 26 ], modulating neuronal activity [ 27 , 28 ], improving bone healing [ 29 , 30 ], and cartilage regeneration [ 31 35 ]. In this study, we investigated the promoting effects and mechanisms underlying LIPUS stimulation on the chondrogenic differentiation of human umbilical cord mesenchymal stem cells (hUC-MSCs) and further evaluated its regenerative application value in articular cartilage defects in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-intensity pulsed ultrasound (LIPUS), a form of ultrasound delivers at a low intensity and outputs in the mode of pulsed waves, has been demonstrated as adjuvant physical therapy, including promoting the differentiation of stem cells [ 22 , 23 ], inhibiting inflammatory responses [ 24 ], accelerating soft tissue regeneration [ 25 , 26 ], modulating neuronal activity [ 27 , 28 ], improving bone healing [ 29 , 30 ], and cartilage regeneration [ 31 35 ]. In this study, we investigated the promoting effects and mechanisms underlying LIPUS stimulation on the chondrogenic differentiation of human umbilical cord mesenchymal stem cells (hUC-MSCs) and further evaluated its regenerative application value in articular cartilage defects in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we verified the safety of LIPUS stimulation and hUC-MSC transplantation-based cartilage repairing procedure. LIPUS non-invasively delivers mechanical stimulation to biological tissues without thermal activity and has been extensively exploited as a therapeutic tool in tissue engineering research, including cartilage regeneration [ 31 35 ]. However, it remains vital to determine and validate the LIPUS parameters for its safe and effective use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-intensity ultrasound had a similar effect on the activation of connective tissue cells, such as human osteoblast-like cell lines and HPDLCs (Jiang et al, 2019). There is also evidence from a recent study on a porcine model that the application of LIPUS on the oral mucosa expedites the repair of the masticatory mucosa (Chauvel-Picard et al, 2021). However, soft-tissue healing remains less studied than bone healing area.…”
Section: Soft-tissue Regenerationmentioning
confidence: 99%
“…The interest in LIPUS appeared about two decades ago with research on their use in biological media. Many studies have shown the ability of LIPUS to stimulate bone, cartilage, tendon and mucosal regeneration [11][12][13][14][15]. At the cellular level, ultrasound promotes the synthesis of collagen by fibroblasts, the formation of bone matrix by osteoblasts, the differentiation of bone mesenchymal stem cells (BMSC) in osteoblasts on titanium surfaces and the synthesis of aggrecan in chondrocytes.…”
Section: Introductionmentioning
confidence: 99%